Effects of Thermal Annealing on the Properties of Zirconium-Doped MgxZn1−XO Films Obtained through Radio-Frequency Magnetron Sputtering - Wen-Yen Lin; Feng-Tsun Chien; Hsien-Chin Chiu; Jinn-Kong Sheu; Kuang-Po Hsueh (Membranes, 2021)
Zirconium-doped MgxZn1−xO (Zr-doped MZO) mixed-oxide films were investigated, and the temperature sensitivity of their electric and optical properties was characterized. Zr-doped MZO films were deposited through radio-frequency magnetron sputtering using a 4-inch ZnO/MgO/ZrO2 (75/20/5 wt%) target. Hall measurement, X-ray diffraction (XRD), transmittance, and X-ray photoelectron spectroscopy (XPS) data were obtained. The lowest sheet resistance, highest mobility, and highest concentration were 1.30 × 103 Ω/sq, 4.46 cm2/Vs, and 7.28 × 1019 cm−3, respectively. The XRD spectra of the as-grown and annealed Zr-doped MZO films contained MgxZn1−xO(002) and ZrO2(200) coupled with Mg(OH)2(101) at 34.49°, 34.88°, and 38.017°, respectively. The intensity of the XRD peak near 34.88° decreased with temperature because the films that segregated Zr4+ from ZrO2(200) increased. The absorption edges of the films were at approximately 348 nm under 80% transmittance because of the Mg content. XPS revealed that the amount of Zr4+ increased with the annealing temperature. Zr is a potentially promising double donor, providing up to two extra free electrons per ion when used in place of Zn2+.